UNDERSTANDING OF EMPLOYMENT SATISFACTION AND EMPLOYEE RETENTION IN PT PABRIK KERTAS TJIWI KIMIA, TBK: A BIBLIOMETRIC STUDY - Haryawan, Beny; Sopiah, Sopiah (International Journal of Business, Law, and Education, 2023)
The purpose of this bibliometric study is to investigate the factors that contribute to job satisfaction and staff retention at PT. Tjiwi Kimia, Tbk Sidoarjo. This research intends to provide in-depth knowledge of the factors influencing work satisfaction and its link with employee retention in the specific context of PT. Tjiwi Kimia Sidoarjo by conducting a systematic review of scholarly literature. The goal of this research is to provide an in-depth understanding of these elements. The purpose of this study is to provide significant insights into improving job satisfaction and retention tactics in the firm that was mentioned by analysing trends, essential concepts, and influential literature